Hot Water Epilepsy (HWE) - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Seizures precipitated by very hot water-head baths (40-50° C), a regional religious custom, or showers were seen in 279 patients between 1980-83 in Bangalore, Southern India, and are reported from the Depts of Neurology and Biostatistics, National Institute of Mental Health and Neurosciences, Bangalore, India, and the Neuroepidemiology Branch, National Institute of Neurological Disorders, NIH, Bethesda, MD, USA.